Sustainable Supply Chains and Digital Transformation. - Tiwari, Saurabh; Goel, Richa (CRC Press, 2025)
This book focuses on the impact of digitalization on supply chains and how it is affecting every aspect of people's lives. It covers the operational changes that are happening in organizations due to the use of technologies such as IoT, cloud computing, smart sensors, electric vehicles, blockchain, AI, drones, smart factories, smart logistics, and smart warehouses. Additionally, it explores how digitalization is helping organizations achieve sustainability through methods like life cycle costing, carbon emission reduction, green supply chains, and recycling technologies.Sustainable Supply Chains and Digital Transformation includes case studies, and exploratory studies utilizing quantitative analysis, scientific and qualitative studies to demonstrate how innovation and technology in supply chains contribute to business sustainability in emerging economies and the global economy and discusses the impact of digitalization on supply chains from both operational and sustainability perspectives.Corporate executives, entrepreneurs, government officials, professionals, academics, postgraduate students, and research associates will undoubtedly find this book to be a valuable addition to their libraries.
Keywords: Supply chain management.; Information technology -- Economic aspects.; Technological innovations -- Economic aspects.; elektronické knihy; electronic books